F -3
G 3
H 6
I. 9
Answer:
f(3) = 9
Step-by-step explanation:
Wherever you see an x on the right, put a 3 in for that x
f(x) = 2x^2 + x - 12
f(3) = 2*(3)^2 + 3 - 12
f(3) = 2*9 + 3 - 12
f(3) = 18 + 3 - 12
f(3) = 9
5 - 10x - 3x2 = 0
Answer:
Step-by-step explanation:
I have enclosed a picture of the quadratic formula because I cannot seem to write the proper formula since it wont let me
✯Hello✯
↪ Alright so first we need to work out values for A B AND C
↪ We need to rearrange this since its the wrong way around
↪ A = -3
B= -10
C= 5
↪ we substitute these values and we get x=0.44 and x=-3.78
❤Gianna❤
A.
5x – 519
B.
5x – 19
C.
5x – 5 • 19
D.
5 + x – 5 + 19
Answer:
74°
Step-by-step explanation:
b + 16°= 90°
b = 74°
the steps to the equation